IN VITRO EVALUATION OF HUMAN TEETH COLOR DIFFERENCES GIVEN BY FOOD DYE TYPE - Alexandru Nemtoi; Irina Calistru (Şlemco); Anca Ignat; Danisia Haba; Ana Nemtoi; Ana Sirghe; Liliana Anchidin-Norocel (Romanian Society of Oral Rehabilitation, 2024)
Dental enamel is an essential structure of teeth, protecting the dentin and the dental nerve sensitive to external stimuli. Certain foods eaten can adversely affect tooth enamel, including food dyes used in colored foods and beverages. The aim of this study was to evaluate the effect of staining (immersion in blueberry, orange, pomegranate juice, carmoisine, tartrazine, and brilliant blue solution) and discoloration (immersion in strawberry and apple juice) on tooth enamel. Also, the impact of time and the pH of the solutions on the staining and discoloration of the tooth enamel will be investigated. Material and methods: Twenty-four human teeth were extracted for orthodontic reasons. Results: The study indicates that prolonged and frequent exposure to food dyes can cause staining or discoloration of tooth enamel, especially when used in high concentrations. The statistical analysis indicates that natural dyes are absorbed faster and color more intensely than synthetic ones, but at the same time, there is a much easier discoloration than synthetic ones, which may be due to the acidic pH. Conclusions: Food dyes can have a negative impact on tooth enamel, causing discoloration, damage, and other changes in its appearance and integrity.